Implementasi Alat Pengujian Relay 48 dan 220 VAC Untuk Mendukung Pratikum di Bengkel Listrik 4 - Arif Andrianto; Susilo; Agus Andryanto; Ilham Syarif Hidayatullah; Nanang Setio Pambudi; Saiful Andani (Elposys: Jurnal Sistem Kelistrikan, 2026)
The Electrical Workshop 4 course at the State Polytechnic of Malang is a form of practicum that aims to improve students' competence in understanding and implementing electrical systems, including the use of relays as regulatory components in automatic control systems. One of the obstacles often encountered is a relay that is damaged or does not function before being used in a student project, causing delays in the learning process and increasing the workload of lecturers in manual che cking. To overcome these problems, this study aims to design and realize a 48 VAC and 220 VAC relay testing tool that can be used as a practicum aid in Electrical Workshop 4. This tool is designed using a step-down transformer to reduce the voltage from 220 VAC to 48 VAC, and is equipped with 8-pin and 11-pin relay sockets for the on-delay and off-delay relay types. The push button is used as a trigger for relay activation, and the indicator light functions as a marker for the success of the relay. The assembly and testing process of the tool was carried out in the Electrical Workshop, and the implementation results showed that the tool was able to function properly according to plan and could be operated by students. In addition, this research also produced a user manual and a scientific article that has been submitted to the Elposys journal.